2023
DOI: 10.3390/nu15133039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Probiotic and a Synbiotic on Body Fat Mass, Body Weight and Traits of Metabolic Syndrome in Individuals with Abdominal Overweight: A Human, Double-Blind, Randomised, Controlled Clinical Study

Abstract: L. fermentum strains K7-Lb1, K8-Lb1 and K11-Lb3 were found to suppress Th1 and Th2 response and to enhance defensin release by enterocytes, respectively. Based on these anti-inflammatory actions, we investigated the effect of these strains on traits of metabolic syndrome, which is driven by low-grade inflammation. In a double-blind, randomised, placebo-controlled clinical trial with three parallel arms, 180 individuals with abdominal overweight were administered for 3 months with (1) placebo; (2) probiotic, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…NUP155 expression in TCGA dataset was investigated at different pathological or clinical stages of pan-cancer using statistical methods, including Kruskal-Wallis Test and Dunn’s test [ 26 28 ]. When the data comprised < 3 samples or the standard deviation of the data was 0, stages I and II were combined for early-stage tumors or stages III and IV were combined for late-stage tumors before performing statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…NUP155 expression in TCGA dataset was investigated at different pathological or clinical stages of pan-cancer using statistical methods, including Kruskal-Wallis Test and Dunn’s test [ 26 28 ]. When the data comprised < 3 samples or the standard deviation of the data was 0, stages I and II were combined for early-stage tumors or stages III and IV were combined for late-stage tumors before performing statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Reasonable assumptions regarding the clinical utilization of Bacteroides have been formulated based on animal experiments and clinical studies involving other probiotics. For the recommended clinical dosage of Bacteroides , we hypothesized that a daily dose ranging from 2 × 10 8 to 1 × 10 10 colony forming units (CFU) ( Silva-Sperb et al, 2019 ; Laue et al, 2023 ) is suitable for healthy adults. This dosage range is considered safe and effective.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The gut microbiome is considered a key factor in the development of NAFLD [ 59 ], so the regulation of the intestinal microecology is a crucial focus for future NAFLD treatments. In recent years, the clinical research on synbiotics for NAFLD treatment has shown promising results [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. The selection of appropriate probiotics and prebiotics to improve NAFLD progression is becoming increasingly feasible and predictable.…”
Section: Synbiotic Compounds For Nafld Treatmentmentioning
confidence: 99%